Deepblue Partners Easy Hot Water / Nur Adiba Lyana Rosli - Rosli, Nur Adiba Lyana (2020)
The concept of the product by DeepBlue Partners is a product that fills the gap and weaknesses of kettles. This product is called Easy Hot Water as it is a product that is easy to use and functions as a water heater where it heats up the water until it is boiled. This product revolves around the concept of portability, functionality and extra safety measures for customer’s comfort.